The Relationship Between the Level of Understanding of Intermittent Fasting and Self-Motivation Behavior Toward the Risk of Increased Blood Glucose in Patients with Diabetes Mellitus - Putri, Gt. Indah M.; Saherna, Jenny; Kirana, Rita; Linda (Fakultas Kedokteran, Universitas Papua, 2025)
Intermittent Fasting is a nonpharmacological approach that can be applied in patients with Diabetes Mellitus to support blood glucose control; however, its implementation requires an adequate level of understanding and strong self-motivation. This study aimed to analyze the relationship between the level of understanding of Intermittent Fasting and self-motivation toward the risk of increased blood glucose in patients with Diabetes Mellitus. A quantitative approach with a correlational cross-sectional design was employed, involving 66 respondents. Data were analyzed using the Spearman rank correlation test. The results demonstrated a significant relationship between the level of understanding of Intermittent Fasting and self-motivation (r = 0.375; p = 0.002), indicating a positive direction with a weak correlation strength. These findings suggest that a better level of understanding of Intermittent Fasting tends to be associated with higher self-motivation in the context of controlling the risk of increased blood glucose. Structured education regarding Intermittent Fasting may therefore be considered as a strategy to support motivation and healthy lifestyle behaviors among patients with Diabetes Mellitus.